Femoro-patellar overstuffing in total knee replacement: assessment of functional implications. Issue 6 (30th June 2021) - Abcha, Oussama; Ammar, Ameni; Daghfous, Mohamed Samir
Introduction: Patellofemoral overstuffing is the situation in which the antero-posterior size of the patella and / or femur is increased after total knee arthroplasty. There is a debate in the literature as to whether or not patellofemoral joint overstuffing has a clinically significant effect on post-operative outcomes. Objectives: Our goal was to determine the influence of femoro-patellar overstuffing on the functional outcome of total knee arthroplasty. Methods: It was a retrospective study of 50 total knee arthtroplasty without Patellar resurfacing, with a minimum follow-up of 12 months. We retrospectively collected epidemiological, clinical, therapeutic and evolutionary data. We performed our measurements on standard knee X-ray preoperatively and postoperatively according to the Beldman method. We calculated trochlear overstuffing, condylar overstuffing and distal femoral overstuffing which is primary endpoint. We have considered significant femoropatellar overstuffing when it is more than 15%. We evaluated the functional repercussions of femoro-patellar overstuffing at follow-up, on pain, mobility and the Western Ontario and McMaster Universities osteoarthritis index functional score (WOMAC). Results: This study shows that an increase in anterior femoral offset, posterior condylar offset and distal femroal diameter are associated with worse patient reported pain and function after total knee arthroplasty. Both Condylar and distal femoral overstuffing were statistically significant with all scores (P<0.05). Conclusion: we found that the overstuffed knees after total knee arthoplasty were more painful, stiffer and with lower physical function. Surgeon could take more care during the anterior and posterior femoral resection in order that the offset is not increased following implant insertion.